Model Pembelajaran Literasi Kritis dalam Pembelajaran Bahasa Indonesia: Studi Kasus di Sekolah Menengah Kejuruan - Yudha Mukti, Ahmad Permana; Wicaksana, Muhlis Fajar; Pardyatmoko, Pardyatmoko (ppjbsip, 2025)
The low reading literacy achievement of vocational high school students in Indonesia indicates the need for learning strategies that foster critical thinking skills. This study aims to develop and test a critical literacy learning model in Indonesian language learning in vocational high schools. Critical literacy is defined as the ability to understand texts in depth, analyze the ideology behind them, and reflect on social reality. The study used a qualitative descriptive approach through a case study and involved 49 students as respondents. Data were collected through a Likert scale questionnaire and open-ended questions, then analyzed using the Miles & Huberman interactive analysis technique. The results showed that the majority of students felt the learning model helped them understand texts, think critically, and actively participate in discussions. Activities such as contextual learning, group discussions, and the use of media were proven to increase student participation and reasoning skills. However, the ability to write personal opinions remained low, indicating the need to strengthen the aspect of reflective expression. Critical literacy learning implemented in a participatory and meaningful manner can shape vocational high school students into individuals who are not only academically competent, but also sensitive to social issues and able to think logically and empathetically. This model is considered relevant to be integrated into the Indonesian language curriculum in vocational high schools consistently. Abstrak Rendahnya capaian literasi membaca siswa SMK di Indonesia menunjukkan perlunya strategi pembelajaran yang menumbuhkan kemampuan berpikir kritis. Penelitian ini bertujuan mengembangkan dan menguji model pembelajaran literasi kritis dalam pembelajaran Bahasa Indonesia di SMK. Literasi kritis dimaknai sebagai kemampuan memahami teks secara mendalam, menganalisis ideologi di baliknya, serta merefleksikan realitas sosial. Penelitian menggunakan pendekatan deskriptif kualitatif melalui studi kasus dan melibatkan 49 siswa sebagai responden. Data dikumpulkan melalui angket skala Likert dan pertanyaan terbuka, kemudian dianalisis dengan teknik analisis interaktif Miles & Huberman. Hasil menunjukkan bahwa mayoritas siswa merasa model pembelajaran membantu mereka memahami teks, berpikir kritis, dan terlibat aktif dalam diskusi. Kegiatan seperti pembelajaran kontekstual, diskusi kelompok, dan penggunaan media terbukti meningkatkan partisipasi dan daya nalar siswa. Namun, kemampuan menulis pendapat pribadi masih rendah, menunjukkan perlunya penguatan pada aspek ekspresi reflektif. Pembelajaran literasi kritis yang diterapkan secara partisipatif dan bermakna mampu membentuk siswa SMK menjadi individu yang tidak hanya kompeten secara akademis, tetapi juga peka terhadap isu sosial dan mampu berpikir secara logis dan empatik. Model ini dinilai relevan untuk diintegrasikan dalam kurikulum Bahasa Indonesia di SMK secara konsisten.